A Financial Issue, a Relationship Issue, or Both? Examining the Predictors of Marital Financial Conflict - Jeffrey P Dew; Robert Stewart (Journal of Financial Therapy, 2012)
This study examines whether financial conflict arises because of financial difficulties, marital problems, or both. Using a recent nationally representative sample of over 1500 married couples, this study finds that economic pressure, communication issues, and deeper “hidden” issues within marriage are all associated with financial conflict. Specifically, economic pressure is positively associated with financial conflict. When spouses report satisfying communication, respect, commitment, and fairness and have equal levels of economic power, they report lower levels of financial conflict. These results suggest that financial conflict is a complex marital phenomenon that both marital therapists and financial counselors may help reduce.
Keywords: Commitment; Communication; Economic Pressure; Financial Conflict; Marital Quality